Developing an Inclusive Approach to the Evaluation of Networked Learning: The ELAC Experience - Asensio, Mireia; Hodgson, Vivien; Saunders, Murray (Proceedings of the International Conference on Networked Learning, 2006)
In this paper we will outline an evaluation approach that was undertaken in the context of the ELAC project. ELAC is an EU funded collaboration between Latin American partners in Costa Rica, Nicaragua and Mexico and European partners in Denmark, Spain and the UK. It is a demonstration project that is assisting the Latin American partners to establish the necessary infrastructure to support online continuing professional education and, in addition, is developing online courses that are intended to be of a networked and collaborative nature. Evolution of project experience will be discussed as it is mirrored in the evolution of the presence of evaluation within the work of the project participants and, more specifically, the development of online courses. The theory and justification for inclusive evaluation will be outlined and analysed and the design of participant activities will be discussed in the light of the tools and sequence of development of an evaluation approach in practice. The core element of the paper is an account of how participants undertook the development of their own evaluation framework on the basis of the interventions of the evaluation team over time.